2021
DOI: 10.1002/ehf2.13576
|View full text |Cite
|
Sign up to set email alerts
|

NT‐proBNP/BNP ratio for prognostication in European Caucasian patients enrolled in a heart failure prevention programme

Abstract: Aims Guidelines support the role of B‐type natriuretic peptide (BNP) and amino‐terminal pro‐BNP (NT‐proBNP) for risk stratification of patients in programmes to prevent heart failure (HF). Although biologically formed in a 1:1 ratio, the ratio of NT‐proBNP to BNP exhibits wide inter‐individual variability. A report on an Asian population suggests that molar NT‐proBNP/BNP ratio is associated with incident HF. This study aims to determine whether routine, simultaneous evaluation of both BNP and NT‐proBNP is warr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
2
1
0
1
Order By: Relevance
“… 19 , 20 , 21 , 22 NT‐proBNP have been demonstrated to be associated with the severity and adverse outcomes of HF. 23 , 24 In our study, we demonstrated that AAT concentration was increased in patients with decreased LVEF. Compared with patients with LVEF ≥ 50%, the serum AAT concentrations were significantly increased in patients with 40% ≤ LVEF < 50% and with LVEF < 40%.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“… 19 , 20 , 21 , 22 NT‐proBNP have been demonstrated to be associated with the severity and adverse outcomes of HF. 23 , 24 In our study, we demonstrated that AAT concentration was increased in patients with decreased LVEF. Compared with patients with LVEF ≥ 50%, the serum AAT concentrations were significantly increased in patients with 40% ≤ LVEF < 50% and with LVEF < 40%.…”
Section: Discussionsupporting
confidence: 53%
“…NT‐proBNP, a neuro‐hormone synthesized in the cardiac ventricles in response to increased wall tension, is an established biomarker of HF 19–22 . NT‐proBNP have been demonstrated to be associated with the severity and adverse outcomes of HF 23,24 . In our study, we demonstrated that AAT concentration was increased in patients with decreased LVEF.…”
Section: Discussionsupporting
confidence: 52%
“…Имеются сведения о том, что более высокий уровень N-терминального фрагмента промозгового натрийуретического пептида (NT-proBNP) у больных без симптомов и признаков недостаточности кровообращения статистически значимо связан с развитием ХСН, независимо от возраста, пола, этнической принадлежности, систолического АД, сахарного диабета, курения, расчетной скорости клубочковой фильтрации (СКФ), препаратов (антигипертензивные средства и статины), индекса массы миокарда левого желудочка (ИММЛЖ) и инфаркта миокарда (относительный риск (RR) =1,95 на 1U логарифмический прирост NT-proBNP, 95% ДИ =1,54-2,46, Р<0,001) [4]. При этом расчетная СКФ, систолическое АД, ИММЛЖ и частота сердечных сокращений были ассоциированы с соотношением NT-proBNP/ BNP в модели линейной регрессии (все P<0,05).…”
Section: материал и методыunclassified
“…They are used in diagnosing and tailoring the management of congestive heart failure [3]. The ESC guidelines included these biomarkers in the risk strati cation for evolution and complications in heart failure patients [4].…”
Section: Introductionmentioning
confidence: 99%